Early detection of metastatic disease through screening ultrasound - Vaz, Bruna (2024)
Screening ultrasound is crucial in emergency care, providing precise guidance for patients in various situations. Its versatility, real-time imaging, and lack of radiation make it invaluable, especially in settings lacking diagnostic resources and specialized expertise. The widespread use of screening ultrasound among health professionals, regardless of their level of sonographic expertise, emphasizes the need for them to manage clinical uncertainties as part of their daily practice." This article emphasizes the crucial role of screening ultrasound, especially in acute abdomen cases. Its integration alongside conventional radiology significantly improves clinical orientation, facilitating prompt treatment decisions and specialist referrals. In a specific case, we reviewed screening ultrasound images, basic abdominal X-rays, and Computed Tomography scans alongside clinical reports to assess initial evaluations made at a peripheral emergency service. Our patient presented with acute abdominal symptoms, revealing suspected liver metastases, free fluid, and signs of intestinal obstruction on ultrasound. These findings were confirmed through Computed Tomography at a referral hospital, showing ultrasound's role in prompt patient triage and transfer. Operator skill is crucial, but comprehensive training minimizes errors. Screening sonography may revolutionize patient safety saving time by detecting pathologies early, preventing overcrowding in emergency departments of reference hospitals. The ultrasonographic detection of images suspected to be metastases is a common occurrence in hospital settings where various advanced diagnostic means, and medical specialties are present. However, the detection of suspicious images of metastases in a pre-hospital context is innovative and provides clinicians with a much better understanding of the patient's clinical landscape.